The Relationship between Mother's Knowledge and Stunting Prevention Behavior in The Patimpeng Community Health Center Work Area - Murni, Murni; Yusuf, Kurnia; Rahmaniar, Andi; St. Masithah; Syafruddin (Miracle Journal of Public Health, 2024)
Stunting is a condition where a child's growth is hampered, resulting in a short body, and the leading cause is malnutrition. This research aims to determine the relationship between maternal knowledge and stunting prevention behavior in children aged 3-5 years. This research used a cross-sectional design with a simple random sampling technique and obtained 68 samples from 80 populations. Analysis was carried out using the Spearman rank test. The results of the Spearman rank test show a p-value <0.05, so it can be concluded that there is a relationship between maternal knowledge and stunting avoidance behavior in children aged 3-5 years in the BLUD UPT Puskesmas Patimpeng District. Bone. Health workers should be able to educate the public about the nutritious food they need